Effects of stage II transport and food bolus sampling methods on the properties of food particles - Tanaka, Yuki; Sugimoto, Hikaru; Kodama, Naoki; Minagi, Shogo (Journal of oral rehabilitation, 2020)
During mastication, some portion of the food bolus is gradually transported to the oropharynx before deglutition, which is known as stage II transport (STII). Although the importance of STII in mastication and deglutition has been widely acknowledged, food particle properties that are transported into the oropharynx by STII have not yet been fully specified. To reveal the food particle properties that are transported into the oropharynx by STII and to assess the usefulness of new food bolus sampling methods for the evaluation of masticatory efficiency. Twenty‐two healthy volunteers participated in this study. Four different bolus sampling conditions were adopted: (a) the whole food particles were expectorated when the subject was aware of the first deglutition, (b) the last bolus to be swallowed at the end of unrestrained food intake was expectorated (aftermost bolus sample), (3) the whole food particles were expectorated when the subject felt ready to swallow after swallow‐inhibited mastication (swallow‐inhibited sample), (4) the particles were regurgitated from the oropharynx after the first STII (stage II‐transported sample). Food particles were analysed using the homogeneity index and particle size index. There was no significant difference between food particles in the aftermost bolus sample and swallow‐inhibited sample. The particles in the stage II‐transported sample showed significantly more homogeneous and smaller sizes than other sampling conditions (P < .05). The food particles transferred to the oropharynx in the stage II‐transported sample were smaller than those broken down by natural mastication.